A Prospective Study on the Outcome of Semi-Closed Neurointensive Care in A Tertiary Care Hospital Located in A Rural Area of Eastern Nepal: A Lower-Income Developing Country - Keyal, Niraj Kumar; Nepal, Pankaj Raj; Tamrakar, Karuna; Bhattarai, Robin; Thapa, Dinesh Kumar; Chaurasiya, Rupesh Kumar (Eastern Green Neurosurgery, 2020)
Background: High mortality and morbidity in neurological patients are found due to lack of closed ICU (Intensive Care Unit), neurointensivist, and training in neurocritical care in most of the developing countries. Therefore, this study was conducted to evaluate the outcome of the neurological patient managed by neurointensivist in a semi-closed ICU. Materials and methods: It was a prospective, descriptive observational cross-sectional study in a level three Neuro-intensive care unit of a tertiary care hospital of Eastern Nepal, for one year in 191 patients. All patients above 18 years admitted to the Neuro-intensive care unit were included in this study. Demographic data was collected for all patients at the time of presentation to the ICU. The outcome of the patient was defined as transferred to Neuro-Ward, leave against medical advice (LAMA), do not resuscitate (DNR) and death. Statistical analysis was done by using SPSS. The result was presented as frequency and percentage. Results: Out of 191 patients, Males (71.7%) was more common than females (28.2%). There were 107 (56%) patients were admitted after 24 hours of injury or illness. 28.2% of patients had a hemorrhagic stroke and was the most common diagnosis for admission in the ICU. This study showed that 58(82.72%) patients survived and were discharged, 23(12%) expired, 7(3.66%) went in LAMA) and 3(1.57%) gave do not resuscitate orders (DNR). Mean days on a mechanical ventilator was 3.17 ± 2.12 days. Mortality in the intubated patient was 19%. Conclusion: A semi-closed Neuro-intensive care unit that includes full-time neurointensivist may have a better outcome than the open ICU.